2021
DOI: 10.1111/cns.13618
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell‐derived mitochondria transplantation: A promising therapy for mitochondrial encephalomyopathy

Abstract: Mitochondrial encephalomyopathies are disorders caused by mitochondrial and nuclear DNA mutations which affect the nervous and muscular systems. Current therapies for mitochondrial encephalomyopathies are inadequate and mostly palliative. However, stem cell‐derived mitochondria transplantation has been demonstrated to play an key part in metabolic rescue, which offers great promise for mitochondrial encephalomyopathies. Here, we summarize the present status of stem cell therapy for mitochondrial encephalomyopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 146 publications
0
13
0
1
Order By: Relevance
“…Although a number of limitations exist for the current treatment of MELAS, gene therapy remains an attractive research direction. Stem cell-derived mitochondrial transplantation has been shown to play an important role in metabolic rescue ( 18 ), which offers hope for the treatment of MELAS. An earlier onset and increased incidence of clinical symptoms corresponds to a worsened prognosis ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of limitations exist for the current treatment of MELAS, gene therapy remains an attractive research direction. Stem cell-derived mitochondrial transplantation has been shown to play an important role in metabolic rescue ( 18 ), which offers hope for the treatment of MELAS. An earlier onset and increased incidence of clinical symptoms corresponds to a worsened prognosis ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the patient was treated with valproate for 4 years before diagnosis, and we replaced valproate with levetiracetam. For mitochondrial diseases, gene therapy is still a popular research topic, and stem cell-derived mitochondrial transplantation has been shown to play a key role in metabolic rescue, which provides promise for mitochondrial encephalomyopathy ( 17 ). To date, there are a total of 49 registered clinical trials of new experimental drugs for the treatment of mitochondrial diseases, and 10 are Phase III trials.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that stem cells can transfer mitochondria to the impaired cells via tunneling nanotubes, extracellular vesicles, or by cellular fusion, helping to revive cell energetics in the recipient cell. Mitochondrial transplantation was shown to be successful in the patients suffering from myocardial IR injury, but it is still far from being implemented in clinical practice [ 72 ].…”
Section: Future Directions and Perspectivesmentioning
confidence: 99%